Validity and Reliability Study of the Indonesian Student Satisfaction with Cultural Simulation Experiences Scale (SCSES) among Nursing Students - Rahmawati, Sephia; Pramukti, Iqbal; Rosidin, Udin (Journal of Nursing Care, 2023)
Virtual Reality is a technology that can simulate a virtual environment like a real one and make it seem like if users can interact in it. The development of learning to use Virtual Reality has begun to be used as a medium for learning skills to increase students' clinical knowledge and reasoning in nursing practice, so that students can show reasonable learning satisfaction in the learning process. Student satisfaction is needed to determine the effectiveness of using VR in nursing practice. Satisfaction with using virtual reality for  student learning experiences can be evaluated using the SCSES (Student Satisfaction with Cultural Simulation Experience Scale), but there is no Indonesian language version for this instrument. This study aimed to translate and adapt the SCSES (Student Satisfaction with Cultural Simulation Experience Scale) instrument in the Indonesia context for nursing students. Methods: The SCSES translation uses the cross-sectional method and in the translation process refers to the five stages of international standard guidelines for translation. Results: The reliability and validity test of the SCSES instrument was tested on 92 Padjadjaran University nursing students. Confirmatory Factor Analysis (CFA) was carried out to measure construct validity. It was found that all items of the Indonesian version of the SCSES instrument were declared valid with the value of all factor loading items > 0.50 and the Cronbach's α test was performed to measure the consistency of measurements (α = 0.964). Conclusions: The Indonesian version of SCSES has good item validity and reliability as a measure of satisfaction in cultural simulation experiences. .